Fabrication of Transparent Spinel Honeycomb Structures by Methyl Cellulose–Based Thermal Gelation Processing. Issue 10 (4th September 2013) - Biswas, Papiya; Rajeswari, Kotikalapudi; Ramavath, Pandu; Johnson, Roy; Maiti, Himadri S.; Krell, A.
<x xml:space="preserve">Abstract</x> Transparent MgAl2O4 spinel of flat as well as honeycomb structure was fabricated by employing thermally induced gel casting of the slurry with 56 wt% solid loading containing 0.2 wt% of methylcellulose. The green specimens were pressureless sintered to 98%–99% of theoretical density with no open porosity at an optimum temperature of 1700°C. Final densification by hot isostatic pressing of both the specimens at the optimum temperature of 1800°C and 195 MPa pressure enabled further elimination of residual porosities and full densification resulting in theoretical density of 3.58 g/cc. The design of the honeycomb was such that it exhibited a surface area to volume ratio of 0.65 cm2/cm3 and a relative density of 0.69. The hardness of the honeycomb specimens has been found to be 13 GPa, which is at par with the solid specimens processed under identical conditions. Solid specimens of around 4 mm thickness exhibited a transmission of >80% in the visible (0.4–0.8 μm) region. Specimens were also tested according to ASTM procedures and have shown a flexural strength (σf) of 195 MPa and plane‐strain fracture toughness (KIc) of 1.87 MPa·m1/2 as reported in this study.